How to overcome the implementation gap in ecosystem services? A user-friendly and inclusive tool for improved urban management. (November 2017) - Levrel, Harold; Cabral, Pedro; Feger, Clément; Chambolle, Mélodie; Basque, Damien
Abstract: One of the main issues with the concept of ecosystem services is its absence on the ground in concrete operational decision-making contexts; that is, an implementation gap. In this study, we investigated if this gap could be overcome through the use of open-source data and free tools, and the adoption of a short-term participatory process. We tested these methods in the context of a project in the urban metropolitan area of Bordeaux (Communauté urbaine de Bordeaux: CUB) in France. The ecosystem services were defined using a participatory approach involving local stakeholders, and then selected scenarios were simulated to test the impact of various development or conservation plans. The study addressed three main questions: (1) Is it possible to adopt a simple methodological approach that overcomes the implementation gap through the development of a user-friendly and inclusive method? (2) What is the added value of a participatory approach? (3) With regards to four scenarios in this territory, what are the ES trends in the selected biophysical and monetary indicators, and will knowledge of these trends help planners to shape a sustainable trajectory for the territory?